1988
DOI: 10.1007/bf01537825
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and temperamental correlates of Type A in children and adolescents

Abstract: Emotional and behavioral correlates of Type A behavior in children and adolescents were examined in 184 fifth-, seventh-, and ninth-grade students, classified as high or low Type A, using self-report, teacher ratings (fifth grade only), and structured interview procedures. Measures included the Hunter-Wolf A-B Rating Scale, Behavioral Symptoms of Stress Inventory, Dimensions of Temperament Survey, Desire for Control Scale, Eysenck Personality Inventory, and the Multiple Affect Adjective Checklist. High Type A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Furthermore, MYTH Impatience, and to some extent also observed Impatience, were related to external criteria in a way which would be expected for the hyperactivity construct. An interesting speculation is one by Heft and colleagues (1988), suggesting that Type A behavior may evolve from a more global and less differentiated pattern of emotional and behavioral arousal in youngsters.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MYTH Impatience, and to some extent also observed Impatience, were related to external criteria in a way which would be expected for the hyperactivity construct. An interesting speculation is one by Heft and colleagues (1988), suggesting that Type A behavior may evolve from a more global and less differentiated pattern of emotional and behavioral arousal in youngsters.…”
Section: Discussionmentioning
confidence: 99%
“…Examining the emotional correlates of the TABP in adolescents, Heft et al (1988) reported that those participants classified as high Type A on the Hunter-Wolf A-B Rating Scale reported a significantly higher level of anger than low-Type As on the Behavioral Symptoms of Stress Inventory. Using 160 fifth-, seventhand ninth-grade students, Thoresen, Eagleston, Kirmil-Gray, and Wiedenfeld (1989) found that high-Type A adolescents (classified by the Hunter-Wolf ) reported significantly more frequency, duration, and magnitude of anger; more anger-in, anger-out, and general anger; and more hostility, suspiciousness, and self-criticism than low-Type A participants.…”
mentioning
confidence: 98%
“…Among them, the French version (α = .7) (Alain, 1989), German (α = .77) (Braukmann, 1981), Dutch (α = .77) (Gebhardt, & Brosschot, 2002), Greek (α = .84) (Pierro, Lavinia, & Raven, 2008), Turkish (α = .75) (Egrigozlu, 2002) and Kuwaiti (α = .65) (Hamadah & Abdullatif, 2000). The adaptations to specific contexts has also been successful: the scale for children (α = .81) (Heft et al, 1988); the scale for health contexts (α = .84) (Smith, Wallston, Wallston, Forsberg, & King , 1984); the scale for dental treatment (α = .68) (Logan, Baron, Keeley, Law, & Stein, 1991); the scale combined with anxiety (α = .81) (Moulding, Kyrios, Doron, & Nedeljkovic , 2009) and the scale for examination contexts (α = .74) (Wise, Roos, Leland, Oats, & McCrann, 1996).…”
mentioning
confidence: 99%